MOTHERHOOD AS SOCIAL INSTITUTE OF MODERN SOCIETY - N. V. Bystrova; C. E. Plotnikova (Вестник Мининского университета, 2017)
Motherhood is one of the most important institutions of modern society. Watching the development of motherhood can be traced to the changes occurring in society. This institution as a mirror reflects all the processes occurring in society, economy, culture, politics, the spiritual realm. That is why the problem of motherhood - a problem across society that affect all areas of its activities. The article deals with the concept of parent school as the most important stage of the continuous education system and its importance in improving the quality of education of children of preschool age. Expands to the current understanding of the phenomenon of maternal school, discusses the functions of the parent school: emotional and intuitive, communicative, value-oriented, School health, psychotherapy, socializing, education.